THE POTENTIAL CIBERANG RIVER ANALYSIS FOR DRINKING WATER SUPPLY DEVELOPMENT OF BANTEN PROVINCE - Ira Mulyawati; Indah Rachmatiah Siti Salami; Arwin Sabar; Mariana Marselina; Hernita Nasir (Universitas Trisakti, 2022)
Aim: This study was aimed to analyze the potential of water sources in the Ciberang River to support drinking water supply system of Banten Province. Methodology and results: The method use to analyze the potential of Ciberang river is a hydrological statistical analysis. The results of the hydrological statistical analysis show that the water resources of the Ciberang River are not sufficient to meet domestic and industrial water needs in Banten Province. Domestic and industrial water demand in Banten Province in 2025 is estimated at 14.64 m3/s and 10.46 m3/s, respectively, while the mainstay discharge with the return period of 10 and 20 year for all durations does not meet these water needs. The mainstay discharge of the Ciberang River with a 10-year return period of 1, 2, 7, 15 and 30 day respectively was 0.08 m3/s, 0.1 m3/s, 0.19 m3/s, 0.36 m3/s, and 0.87 m3/s. The mainstays of the 20-year return period of 1,2,7,15 and 30 day respectively are 0.04 m3/s, 0.06 m3/s, 0.11 m3/s, 0.23 m3/s and 0.59 m3/s. Conclusion, significance, and impact study: Based on this, it is necessary to conserve water resources to increase the main flow of the Ciberang River. One of the strategic policies to increase the river's mainstay discharge is constructing the reservoir.